IMPACT OF SEED PRIMING IN BOOSTING COTTON GERMINATION AND YIELD IN WARM AREAS - IQBAL, MJ; LUQMAN, RD; YOUNAS, HS; FARID, I; NIAZ, A; KHAN, ZA; NAZ, R; KHALID, S; SHAHZAD, S; KALSOM, A (Biological and Clinical Sciences Research Journal, 2024)
Cotton (Gossypium hirsutum L) has a high-ranked and exceptional position in the farming system of the globe. It is mainly grown during the kharif season. High temperature is one of the restricting and consistently approaching dangers to cotton efficiency in Pakistan. It has given a big loss in the recent few years. The plant parts like seedlings, bolls, and fiber quality attributes are incredibly affected because of high temperature. Production of cotton is decreasing due to many reasons mainly pest infestation and high temperatures. To fill the yield gap, an experiment was conducted in which different concentrations of plant extracts i.e. Sugar Beet Root Extract (1%), Watermelon Juice (1%), Moringa Leaf Extract (1%), Jantar Leaf Extract (1%), Spanish Leaf Extract (2%), Carrot Root Extract (1%), Ginger Root Extract (1%), and Lemon Juice (1%) were used. All growth-promoting substances had a significant impact on crop growth and yield attributes. However, maximum yield was associated with priming of seeds with moringa leaf extract (3%). Germination percentage (86.5), number of bolls plant-1(54.7), yield (3.5 tons ha-1), biological yield (11.8 tons ha-1), and harvest index (31.5) were significantly boosted by moringa leaf juice as priming agent. Based on the experiment, different parameters on the growth and yield of cotton were examined and analyzed statistically by using the least significant digit (LSD) at 5% through standard procedures.